Does DNA extraction affect the specificity of a PCR method claiming the specific detectability of a genome-edited plant? - Sophia Edelmann; Christian Savini; Dominik Moor; Jörn Lämke; Kathrin Lieske; Marco Mazzara; Hendrik Emons; Joachim Mankertz; Christopher Weidner (GM Crops & Food)
Under current EU legislation, genetically modified organisms (GMOs) and derived food and feed products must be authorized as GM food, feed, or seed and appropriate detection methods must be made available for use in official controls. A Real-Time PCR method has recently been published by Chhalliyil et al. claiming to be specific for the detection and identification of genome-edited oilseed rape (OSR) lines commercialized in North America. In a previous study, we have independently assessed this method in three reference laboratories for sensitivity, specificity, and robustness. We found that the method does not meet all the minimum performance requirements (MPR) for GMO testing in the EU, which contradicts the claims of the method developer. Here we show, in addition to the previously published method assessment study that a modified DNA extraction is not the reason for the contradictory findings and does not affect the specificity of the method. We also discuss the procedures recently proposed by the method developers for interpreting PCR results with high Cq values.